Out of step : NIEM and N-DEx two national data-sharing initiatives face major challenges. - Kurlander, Neil
Since the horrific events of September 11, 2001, the federal government has intensified its efforts to improve communications, collaboration and information sharing between government and private sector agencies at all levels. The task of creating a seamless system of data and communication between disparate agencies has faced both technological and political obstacles.